2010
DOI: 10.1007/s00405-010-1437-2
|View full text |Cite
|
Sign up to set email alerts
|

Extra-major salivary gland pleomorphic adenoma of the head and neck: a 10-year experience and review of the literature

Abstract: Pleomorphic adenomas, or benign mixed tumors, make up 65% of all salivary gland tumors. They also can be found as solid tumors in other parts of the head and neck region, such as the auditory canal, the eyelids, and the orbital area. In this study, we investigated extra-major salivary gland pleomorphic adenomas of the head and neck region retrospectively at a tertiary care center. Between March 1998 and June 2009, 37 patients underwent primary surgery for extra-major salivary gland pleomorphic adenoma of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…A review of publications in English (MEDLINE 1966-2012) was performed, with all cases reported as carcinoma ex-pleomorphic adenoma, malignant mixed tumor, carcinoma ex-mixed tumor of the sinonasal tract included in the review [8][9][10][11][12][13][14][15][16][17][18]. However, many cases were excluded if the lesion arose primarily in the oral cavity, upper lip or oropharynx or represented a different tumor type, or if the information was too generalized and nonspecific to make a meaningful interpretation of the demographics, histologic features, or patient outcome.…”
Section: Methodsmentioning
confidence: 99%
“…A review of publications in English (MEDLINE 1966-2012) was performed, with all cases reported as carcinoma ex-pleomorphic adenoma, malignant mixed tumor, carcinoma ex-mixed tumor of the sinonasal tract included in the review [8][9][10][11][12][13][14][15][16][17][18]. However, many cases were excluded if the lesion arose primarily in the oral cavity, upper lip or oropharynx or represented a different tumor type, or if the information was too generalized and nonspecific to make a meaningful interpretation of the demographics, histologic features, or patient outcome.…”
Section: Methodsmentioning
confidence: 99%
“…The English literature contains many case reports, small series, and a few larger series, all of which focus on a particular feature. Specifically, the series often present all salivary gland tumor types together [39,40,57,67,89,91,97,99,106,[120][121][122][123][124][125][126][127], encompass all head and head anatomic sites, describe adenoid cystic carcinoma only but in all sites [5, 6, 12, 17, 22, 31, 32, 35, 39, 47, 50, 52, 57, 59, 66, 73, 75, 76, 87, 91-93, 98, 100, 101, 106, 112, 113, 117, 128-130], or only one subsite but all tumors combined. Many small series focus on the radiographic findings alone [36, 62, 88, 96, 99, 108-110, 112, 117, 131-134], or specifically address a particular therapy (radiation) [8,20,24,25,33,54,63,66,69,86,92,95,111] for all tumor types of a particular anatomic site.…”
Section: Introductionmentioning
confidence: 99%
“…There was no sex predilection. Common symptoms related to primary PA of the EAC included obstruction of the EAC meatus, hearing loss, otalgia, and otorrhoea [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…However, PA may also arise from the external auditory canal (EAC), although reports are very rare. Since 1951, when Mark and Rothberg published their first EAC pleomorphic adenoma report [2], at least 35 similar cases have been reported [3][4][5][6][7][8][9][10][11][12][13]. PA of the EAC is classified as a type of ceruminal gland tumour.…”
Section: Introductionmentioning
confidence: 99%